1982
DOI: 10.1073/pnas.79.21.6727
|View full text |Cite
|
Sign up to set email alerts
|

Initial synaptic transmission at the growth cone in Xenopus nerve-muscle cultures.

Abstract: The excellent visibility ofcultured cells allows the early events during formation of the neuromuscular junction to be suitably studied. It has been shown in various culture systems that synaptic transmission occurs early after nerve-muscle contact. Early synaptic potentials are small in amplitude and slow in time course reflecting a low acetylcholine receptor density at the site of nerve contact. Acetylcholine receptors accumulate later at the contact region. We have examined initial synaptic transmission at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 21 publications
(24 reference statements)
2
27
0
Order By: Relevance
“…Our observation that presynaptic exocytotic machinery can develop in the absence of postsynaptic receptors agrees with previously published studies showing that nerve-muscle synapses form in the presence of antagonists that block receptor function (Cohen, 1972;Ding et al, 1983;Landmesser and Szente, 1986). Our results are also consistent with the findings that dissociated spinal neuron somas and associated growth cones are capable of both spontaneous (Kidokoro and Yeh, 1982;Hume et al, 1983;Young and Poo, 1983;Chow and Poo, 1985) and evoked (Sun and Poo, 1987) transmitter release. However, studies using Xenopus have further indicated that responses to both spontaneous and stimulusevoked release of ACh from spinal neurons are potentiated on contact with muscle.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our observation that presynaptic exocytotic machinery can develop in the absence of postsynaptic receptors agrees with previously published studies showing that nerve-muscle synapses form in the presence of antagonists that block receptor function (Cohen, 1972;Ding et al, 1983;Landmesser and Szente, 1986). Our results are also consistent with the findings that dissociated spinal neuron somas and associated growth cones are capable of both spontaneous (Kidokoro and Yeh, 1982;Hume et al, 1983;Young and Poo, 1983;Chow and Poo, 1985) and evoked (Sun and Poo, 1987) transmitter release. However, studies using Xenopus have further indicated that responses to both spontaneous and stimulusevoked release of ACh from spinal neurons are potentiated on contact with muscle.…”
Section: Discussionsupporting
confidence: 82%
“…Postsynaptic modulation of transmitter release machinery has been provided from studies that use Xenopus nerve and muscle wherein the formation of synaptic contacts can be strictly controlled. Measurement of synaptic responses from myocytes shows that both motor neuron somas and growth cones can spontaneously release ACh before contact with muscle (Kidokoro and Yeh, 1982;Hume et al, 1983;Young and Poo, 1983;Chow and Poo, 1985). However, contact with muscle potentiates transmitter release, as reflected in the increased size (Evers et al, 1989;Liou et al, , 1999 and frequency of spontaneous events (Xie and Poo, 1986;Evers et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Disaggregated cells were then plated onto glass coverslips or plastic tissue-culture dishes and incubated at room temperature (22-24Ā°C) for 24 -48 hr in a medium composed of 49% NFR and 51% L-15 (Life Technologies, Gaithersburg, MD) supplemented with 3 mg/ml glutamine, 0.1 mg/ml insulin, 0.7 mg/ml sodium selenite, 0.6 mg/ml transferrin, 1 mg/ml sodium pyruvate, and 35 ng/ml brain-derived neurotrophic factor [kindly provided by Amgen (Thousand Oaks, CA) and Regeneron (Tarrytown, NY)]. In as little as 12 hr, spinal neurons extended neurites, occasionally elaborating varicose regions on the substrate and in contact with spindle-shaped muscle cells (Kidokoro and Yeh, 1982;Takahashi et al, 1987;Evers et al, 1989;Tabti and Poo, 1994). In 1 and 2 d cultures, the presynaptic contact often takes the form of a varicosity sufficiently large to be accessed with patch electrodes, allowing one to correlate presynaptic electrophysiological events with transmitter release.…”
Section: Methodsmentioning
confidence: 99%
“…The best information available on the probability of forming a synapse comes from elegant studies of neuromuscular junctions in culture. These studies indicate that functional synapses form with high probability within a few seconds after motor neurons contact muscle (Kidokoro and Yeh, 1982;Sun and Poo. 1987;Evers, Laser, Sun, Xie.…”
Section: Discussionmentioning
confidence: 98%
“…Vogel, and Nirenberg, 1973;Bevan and Steinbach, 1977), and presynaptic neurons can package and release transmitter before they encounter a muscle cell (Hume, Role, and Fischbach, 1983;Young and Poo, 1983). A consequence of this precocious development is that functional interactions can be seen as soon as the growth cone arrives at the muscle surface (Frank and Fischbach, 1979;Kidokoro and Yeh, 1982;Sun and Poo, 1987). However, even neuromuscular synapses undergo an extended penod of maturation during which their functional properties are extensively modified (see Purves and Lichtman, 1985 for a review).…”
Section: Introductionmentioning
confidence: 99%